2020
DOI: 10.1111/tbed.13516
|View full text |Cite
|
Sign up to set email alerts
|

Association of brucellosis to abortions in humans and domestic ruminants in Kagera ecosystem, Tanzania

Abstract: Brucellosis is a worldwide zoonotic disease of socio‐economic importance. Understanding the association of this disease with pregnancy outcome has the potential of contributing to the reduction of its reproductive burden in humans and animals among pastoral communities in Tanzania. A prospective cohort study was conducted in Kagera Region on pregnant women (n = 76) and gravid ruminants (121 cattle, 125 goats and 111 sheep). Exposed and non‐exposed groups to brucellosis were followed for 6 months (from 15 Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…In this study, 2 children and 34 adults were diagnosed with orchiepididymitis. According to previous studies, women infected with Brucella suffer from oophoritis, salpingitis, endometritis and others complications, resulting in abortion [13] although the above were not reported in this study. Understanding the damage caused to the reproductive system is helpful in reducing adverse outcomes in pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, 2 children and 34 adults were diagnosed with orchiepididymitis. According to previous studies, women infected with Brucella suffer from oophoritis, salpingitis, endometritis and others complications, resulting in abortion [13] although the above were not reported in this study. Understanding the damage caused to the reproductive system is helpful in reducing adverse outcomes in pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
“…This study detected Brucella in sera from abortive woman, cow and goat. Although there was a failure to detect Brucella from a limited sample size of aborted materials, the detection of Brucella from sera of aborted individuals could raise the same suspicions regarding the contribution of brucellosis to reproductive failure in this pastoral area as reported earlier (Ntirandekura et al, 2020). The failure to detect Brucella species in aborted materials could have been associated to the transport medium used (liquid nitrogen), long time for conservation of samples before analysis (9 months) and the low DNA concentration among other factors.…”
Section: Discussionsupporting
confidence: 55%
“…The samples were collected during previous cross‐sectional and prospective cohort studies conducted in Ngara and Karagwe districts (Figure 1) in June 2017 (personal communication) and November 2017‐ April 2018 in Kagera region, Tanzania (Ntirandekura, Matemba, Kimera, Muma, & Karimuribo, 2020). Five millilitres of venous blood were firstly taken from humans going for malaria checking (July 2017) (personal communication) and from cattle, goats and sheep in the same villages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a previous study reported that brucellosis was found in a fox farm ( 27 ). Molecular tools can support the results from serological tests to avoid cross-reaction with other pathogens ( 28 ). AMOS-PCR results showed the presence of this special 731 bp band in many aborted fetuses' samples.…”
Section: Discussionmentioning
confidence: 99%